Deep-sea litter in the Gulf of Cadiz (Northeastern Atlantic, Spain). (April 2020) - Mecho, Ariadna; Francescangeli, Marco; Ercilla, Gemma; Fanelli, Emanuela; Estrada, Ferran; Valencia, Javier; Sobrino, Ignacio; Danovaro, Roberto; Company, Joan B.; Aguzzi, Jacopo
Abstract: This study describes the distribution and composition of litter from the Gulf of Cadiz (Northeastern Atlantic, Spain), a region of confluence between the Atlantic and Mediterranean, with intense maritime traffic. Several geological features, such as canyons, open slopes and contourite furrows and channels, were surveyed by remotely operated vehicle (ROV) observations between depths of 220 and 1000 m. Marine litter was quantified by grouping the observations into six categories. Our results indicate the presence of markedly different habitats in which a complex collection of different types of litter accumulate in relation to bottom current flows and maritime and fishing routes. This result justifies a seascape approach in further anthropogenic impact studies within deep-sea areas. Highlights: Presence of diversified litter typology was observed at almost all monitored sites. Higher presence of litter occurred in areas with fishing and maritime routes. Higher presence of plastic occurred where bottom current intensity was lower. Observed interactions occurred between fauna and litter.